The outcome of young vs. old gastric cancer patients following gastrectomy: a propensity score matching analysis - Yu-Xi Cheng (BMC, 2021)
Abstract Purpose The purpose of the current study was to compare the postoperative complications, overall survival and disease-free survival in young and old gastric cancer patients after gastrectomy using propensity score matching (PSM). Methods Adult patients (aged ≥ 18 years) who underwent gastrectomy for gastric cancer in a single clinical center from January 2013 to December 2017 were enrolled continuously for retrospective analysis. To minimize the selection bias between the young and old groups, the PSM was conducted in this study. Results A total of 558 patients were included in this study, with 51 patients in the young group (aged ≤ 45 years) and 507 patients in the old group (aged > 45 years). After 1:1 matching according to PSM, 51 patients in the young group were matched to 51 patients in the old group. After PSM, there was no difference in the baseline information. In terms of short-term outcomes, no difference was found in operation time (P = 0.190), intraoperative blood loss (P = 0.336), retrieved lymph nodes (P = 0.948), blood transfusion (P = 0.339), postoperative hospital stay (P = 0.194), or postoperative complications (P = 0.477) between the two groups. For overall survival, no statistically significant difference was found in all stages (P = 0.383), stage I (P = 0.431), stage II (P = 0.875) or stage III (P = 0.446) gastric cancer. Furthermore, regarding disease-free survival, no differences were found between the two groups in all stages (P = 0.378), stage I (P = 0.431), stage II (P = 0.879) or stage III (P = 0.510) gastric cancer. Conclusion Age might not be an independent prognostic factor for short-term outcomes, OS, or DFS in gastric cancer patients who underwent gastrectomy. The pTNM stage of GC might be an independent prognostic factor for OS and DFS.